HYPOTHERMIA AND RENAL TUBULAR VACUOLISATION REVISITED. (February 2015) - Zhou, Chong; Bright, Fiona; Winskog, Calle; Yool, Andrea; Byard, Roger W.
Abstract : Aim: To use a rodent model to evaluate the association between basal vacuolisation and hypothermia. Methods: An established model with anaesthetised, minimally-stressed Sprague-Dawley rats was used. Twenty-eight rats were given free access to food, water, and social interaction to reduce psychological and physiological stress. They were then sequentially anaesthetised and placed into a cooling chamber with continuous monitoring of core body temperature. This study was fully approved by the Animal Ethics Committee at The University of Adelaide. Results: Core temperatures decreased to a minimum of 7–10°C which resulted in death of the animals under anaesthesia at times ranging from 120–240 mins. There was no evidence of basal vacuolisation in any of the renal tubular epithelial cells. Discussion: The diagnosis of hypothermia at autopsy is often difficult as it relies on a series of variable features such as skin discolouration and gastric erosions. Basal lipid vacuolisation in renal epithelial cells has recently been proposed as another diagnostic marker. This study suggests that basal renal tubular cell vacuolisation may not be solely caused by lethal hypothermia but may be a manifestation of a more complex pathophysiological pathway involving the synergistic effects of stress.